Faktor-Faktor Kelelahan Kerja Pada Pekerja di Perusahaan: Literatur Review - Natasha Melfisyaira Putri Pasaribu; Susilawati Susilawati (PT. Alahyan Publisher Sukabumi, 2024)
In a company, the driver of work accidents is work fatigue. Work fatigue factors include internal and external factors. This research aims to analyze the factors that cause work fatigue in workers in one company. The research uses a systematic literature review approach. The data was obtained from various journals available in leading academic databases such as Google Scholar. The data is combined into a structured discussion.The results of the analysis from these journals show that there is a significant relationship between the variables that cause work fatigue in workers in the company.